Post-quantum lightweight symmetric block cipher “Cypress” - Родінко, М.Ю.; Олійников, Р.В. (Radiotekhnika, 2017)
The post-quantum lightweight block cipher “Cypress” is proposed. The encryption algorithm is based on the Feistel network, an ARX-transformation is used as a round function. The block cipher “Cypress” provides a high level of cryptographic strength against exhaustive search attacks (it supports 256 and 512 bits key length). In terms of performance on various hardware and software platforms the proposed cipher “Cypress” significantly exceeds the AES block cipher (2.5-3 times). This block cipher has a compact implementation that does not require the use of pre-calculation tables.